Prescription auditing in Institute of Mental Health and Neurosciences, Srinagar, Jammu, and Kashmir: A prospective study - Syed Sajad Hussain,; Bandy, Mudasir; Zahoor Ahmad Rather, (Asian Journal of Medical Sciences, 2023)
Background: Prescription audit can be described as a tool to evaluate the quality of medical treatment which is being offered to the patients in any health care facility. It can prove to be helpful in devising any effective changes that would improve quality of care to the patients. Aims and Objective: The study was conducted to carry out prescription audit among the psychiatric patients seeking consultation in a tertiary care centre. Materials and Methods: This prospective observational study was conducted on 500 prescriptions for a time period of six months in the outpatient department of Institute of Mental Health and Neurosciences (MHANS). During the study all the prescriptions were collected and evaluated based on WHO prescribing indicators. Data was entered and analyzed using SPSS software version 16.0. Results: Five hundred prescriptions comprising of 1,260 drugs were analyzed. The average number of drugs per prescription was 2.8. There were 52.7% males and 47.3% females. Most patients (49%) were from the age group of 21-40 years. In majority of the cases (90.9%) more than one drug was prescribed and 4.6% (20) of medications were prescribed by generic names. The study revealed that Major Depression Disorder (MDD) was the most common psychiatric morbidity (40%). Clonazepam was the most common drug (19.6%) that was prescribed for the patients irrespective of the diagnosis. Conclusion: Prescription audit can be helpful to evaluate the existing prescription pattern of any health care facility and ensure the rational drug therapy as per WHO prescription parameters.